Design Storyboard dalam mengembangkan Virtual Laboratorium - Purba, Friska Juliana; Haryani , Calandra A. (PendIPA Journal of Science Education, 2024)
The storyboard aims to facilitate the initial stage of creating a virtual laboratory, which can be used to enhance understanding according to different levels and classes. The research method used in this study is Development Research with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation), which is an instructional design model that demonstrates basic steps of an easily executable learning system. The technique used to analyze the product includes suggestions or comments from evaluation results, validation sheets, and reviews from content experts and media experts. The storyboard display greatly facilitates the creation of a virtual laboratory because of its easy-to-understand appearance, which represents the material being delivered. This storyboard will be further developed into the next stage, which is a web-based virtual laboratory.